636 views
5 votes
F(x) = (x + 1)(x - 3)(x - 4)

2 Answers

6 votes
^^^^^^^^^^^^^^^^^^^^^^^^^
User Jaap Joris Vens
by
5.5k points
1 vote

Answer:

f(x) x^3 - 2x^2 + 5x + 12

Explanation:

Next time please share the goal. I'm guessing your intent was to multiply out the given function.

f(x) = (x^2 + x - 3x - 3)(x - 4), or

= (x^2 - 2x - 3)(x - 4)

Now apply the distributive property of multiplication:

f(x) = x^3 - 4x^2 - 2x^2 + 8x - 3x + 12, or

= x^3 - x^2(4 - 2) + x(5) + 12, or

f(x) x^3 - 2x^2 + 5x + 12

User Kshitij Mittal
by
5.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.